Analysis Driviing Force, Pressure, State, Impact And Regional Environmental Issues Kediri City - Yuly Peristiowati; Hariyono (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2023)
The priority issue in the City of Kediri is waste with the number of households served by waste transportation as much as 98.811% and 1.189% unserved. The population is 284,003 people, if 1.189% of the waste is not collected, then the volume of waste generation is 8.57 m3/day (assuming that each person produces 2.5 liters/person/day of waste), a month collected as much as 251.35 m3. The occurrence of river water pollution due to domestic and industrial waste which discharges its liquid waste into water bodies, and the not optimal processing of WWTP in Industry and Hospitals in the City of Kediri. Design This research uses descriptive analysis that explains environmental issues and problems in the city of Kediri. The variables described are: waste processing, water pollution, and air pollution. The results of this study show that most of the waste processing in the city of Kediri (70%) has not yet carried out waste sorting and processing starting from the source (households). Pollution of river water in the city of Kediri is mostly caused by 60% domestic waste, 40% industrial waste. Air pollution in the city of Kediri has not reached a dangerous limit, namely the results of the air quality index in the city of Kediri 86%. The Kediri City government's response included the construction of a Communal WWTP, tightening permits for disposing of liquid waste (IPLC) for industry and requiring industries/business activities that produce wastewater, to make WWTPs. Efforts made by the Kediri city government to minimize air pollution are greening activities with one sub-district, one green open space, while in the transportation sector, through activities such as procuring mass transportation for school children.